Relationship Between Organizational Social Capital and Quality of Work-Life of the Employees - Mohammad Javad Zahedi Mazandarani; Hooshang Nayebi; Parvaneh Danesh; Hossein Nazoktabar (بهبود مدیریت, 2014)
The concept of social capital is used as a tool for understanding the quality of work-life and is known as a basis of organizational excellence. The present study attempts to identify the effects of social capital on the quality of work-life of employees. This study is correlation. The population of the study is all staff of Payame Noor University of Mazandaran that among them, 130 people were selected as a stratified sampling. In this survey have been used two social capital questionnaire of Nahapyt and Ghoshal and also questionnaire of Quality of Walton Work-Life. In this study, the data was analyzed with correlation analysis and structural equation model. SPSS and Lisrel Software are used for data analysis. Test results showed that there is a significant positive correlation between the dimensions of social capital (structural, relational and cognitive) with the quality of work life with %99 confidence and error level smaller than 0/01. Also, SEM analysis indicated that the dimensions of social capital have the power to predict the quality of work life.